FORMATION OF THE SOUTH CASPIAN BASIN AS A RESULT OF PHASE TRANSITIONS IN THE LOWER CONTINENTAL CRUST - Artyushkov E.V. (My University, 2007)
A number of deep troughs with sedimentary sequences no less than 15–20 km thick are known within continents and at their margins. The South Caspian, Near-Caspian, Barents, and Black Sea basins pertain to this category. The thickness of the consolidated crust in their deep parts decreases to 10–20 km, whereas the P-wave velocity increases to the values characteristic of basic rocks. Therefore, this crust is often referred to as oceanic. However, according to, deep parts of the Barents and Near-Caspian basins are underlain by the continental crust. Its subsidence was caused by phase transitions with compaction of basic rocks in the lower crust.